2019
DOI: 10.1177/0269758019895345
|View full text |Cite
|
Sign up to set email alerts
|

The significance of context and victim–offender relationship for Swedish social workers’ understandings of young men’s violent victimization

Abstract: This article investigates how social workers’ interpretations of contextual factors and the relationship between victim and offender affect their understanding and assessment of male violent victimization. The study was designed as a multiple case study with a qualitative comparative approach. Focus group interviews supported by vignettes were used to collect data. Interviews were carried out with professional Swedish social workers working with victimized men and women at support units for young crime victims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…On the other hand, the law explicitly says that social services should consider the need to support women exposed to violence, saying nothing about men, which may be viewed as a form of gender discrimination. A study based on focus group interviews with social workers suggested that the violence to which young men are subjected in cases of street violence and interpersonal violence almost seems unavoidable or even "natural" (Skillmark & Kullberg, 2019). The authors concluded that social workers' attitudes toward young male crime victims may contribute to making these men appear to be less legitimate victims.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the law explicitly says that social services should consider the need to support women exposed to violence, saying nothing about men, which may be viewed as a form of gender discrimination. A study based on focus group interviews with social workers suggested that the violence to which young men are subjected in cases of street violence and interpersonal violence almost seems unavoidable or even "natural" (Skillmark & Kullberg, 2019). The authors concluded that social workers' attitudes toward young male crime victims may contribute to making these men appear to be less legitimate victims.…”
Section: Discussionmentioning
confidence: 99%